Autoantibody against the amino acid sequence 661–680 in apo B-100 is associated with decreased carotid stenosis and cardiovascular events - Fredrikson, Gunilla Nordin; Schiopu, Alexandru; Berglund, Göran; Alm, Ragnar; Shah, Prediman K.; Nilsson, Jan (Atherosclerosis, 2007)
Immunization with malondialdehyde (MDA)-modified peptides corresponding to the amino acid sequence between 661 and 680 in apo B-100 (p45) inhibits atherosclerosis in apo E knockout mice. The same effect can be obtained by treating the mice with recombinant anti-MDA-p45 IgG, suggesting that these antibodies have atheroprotective effects. In the present study we analyzed if autoantibodies against p45 and MDA-p45 are related to carotid atherosclerosis and acute cardiovascular events in humans. Using a nested case control design we determined plasma levels of IgG recognizing native and MDA-modified p45 in baseline samples from 75 subjects with acute myocardial infarction or sudden cardiac death and 148 matched controls. The control group was found to have significantly higher levels of p45 IgG than the cases. Moreover, an independent association was found between high levels of MDA-p45 IgG and a low degree of carotid stenosis ( P = 0.006). There was a high degree of co-variation between IgG binding to native p45 and MDA-p45 ( r = 0.68, P < 0.0001). The associations between lower levels of autoantibodies against the apo B-100 p45 sequence and cardiovascular disease are in agreement with previous experimental studies demonstrating that these antibodies have atheroprotective effects. Our findings support the notion that the p45 sequence of apo B-100 is a potential target for immunomodulatory treatment of atherosclerosis in humans.